PV Interneurons: Critical Regulators of E/I Balance for Prefrontal Cortex-Dependent Behavior and Psychiatric Disorders - Ferguson, Brielle R.; Gao, Wen-Jun (Frontiers in Neural Circuits, 2018)
Elucidating the prefrontal cortical microcircuit has been challenging, given its role in multiple complex behaviors, including working memory, cognitive flexibility, attention, social interaction, and emotional regulation. Additionally, previous methodological limitations made it difficult to parse out the contribution of certain neuronal subpopulations in refining cortical representations. However, growing evidence supports a fundamental role of fast-spiking parvalbumin (PV) GABAergic interneurons in regulating pyramidal neuron activity to drive appropriate behavioral responses. Further, their function is heavily diminished in the PFC in numerous psychiatric diseases, including schizophrenia and autism. Previous research has demonstrated the importance of the optimal balance of excitation and inhibition (E/I) in cortical circuits in maintaining the efficiency of cortical information processing. Although we are still unraveling the mechanisms of information representation in the prefrontal cortex (PFC), the E/I balance seems to be crucial, as pharmacological, chemogenetic, and optogenetic approaches for disrupting E/I balance induce impairments in a range of PFC-dependent behaviors. In this review, we will explore two key hypotheses. First, PV interneurons are powerful regulators of E/I balance in the PFC, and help optimize the representation and processing of supramodal information in PFC. Second, diminishing the function of PV interneurons is sufficient to generate an elaborate symptom sequelae corresponding to those observed in a range of psychiatric diseases. Then, using this framework, we will speculate on whether this circuitry could represent a platform for the development of therapeutic interventions in disorders of PFC function.